1983
DOI: 10.1002/anie.198304401
|View full text |Cite
|
Sign up to set email alerts
|

Bond‐Forming Initiation in Spontaneous Addition and Polymerization Reactions of Alkenes

Abstract: Spontaneous addition and polymerization reactions of alkenes of different electron-densities result in a wide variety of small organic molecules and high polymers. Tetramethylenes are proposed as key intermediates, i. e. resonance hybrids of 1,4-diradical and zwitterionic limiting structures. Their character is determined by the substituents at the terminals: Zwitterionic character is favored by strong donors, such as alkoxy and dialkylamino groups, at the carbenium center and strong acceptors, such as two cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(53 citation statements)
references
References 197 publications
0
52
0
1
Order By: Relevance
“…Hall et al 24.25) proposed a bond-forming initiation theory to explain spontaneous charge-transfer initiation between electrophilic and electron- A v i n cm mcr of CEVE rich olefins. This theory postulates bond formation between the P-carbons to form a tetramethylene intermediate.…”
Section: C)mentioning
confidence: 99%
“…Hall et al 24.25) proposed a bond-forming initiation theory to explain spontaneous charge-transfer initiation between electrophilic and electron- A v i n cm mcr of CEVE rich olefins. This theory postulates bond formation between the P-carbons to form a tetramethylene intermediate.…”
Section: C)mentioning
confidence: 99%
“…Many different initiation and polymerization mechanisms for such donor-acceptor systems have been proposed and reviewed. [5][6][7] The novel aspect of the present process is that the donor (styrene) and acceptor (N-phenyl maleimide) monomers spontaneously copolymerize on aluminum surface in the absence of any externally added initiator. By controlling the solvent quality of the monomer solution the polymerization occurs only at the aluminum-solution interface.…”
Section: Introductionmentioning
confidence: 99%
“…These two groups can form charge transfer complexes of donor-acceptor monomer systems in which MA and CVE act as the accepter monomer and the donor monomer, respectively. 28 It is well known that alternating copolymers of vinyl ether and MA can be formed in free-radical polymerization. [29][30][31][32] Our previous report 21 used 1 H nuclear magnetic resonance to show that the molar composition of MA and CVE of the formed copolymer was 1:1, and the 13 C nuclear magnetic resonance spectrum suggested that these monomers were alternately polymerized.…”
Section: Resultsmentioning
confidence: 99%